Salidroside Inhibits Myogenesis by Modulating p-Smad3-Induced Myf5 Transcription - Peng Zhang; Wenjiong Li; Lu Wang; Hongju Liu; Jing Gong; Fei Wang; Xiaoping Chen; Xiaoping Chen (Frontiers Media S.A., 2018)
Aim: Salidroside is an active compound extracted from Rhodiola rosea which is used to alleviate fatigue and enhance endurance in high altitude regions. Some studies have demonstrated that salidroside can affect precursor cell differentiation in hematopoietic stem cells, erythrocytes, and osteoblasts. The aim of this study was to investigate the effect of salidroside on myoblast differentiation and to explore the underlying molecular mechanisms of this effect.Methods: C2C12 myoblast cells were treated with different concentrations of salidroside in differentiation media. Real-time PCR, Western blotting, and immunofluorescence assay were employed to evaluate the effects of salidroside on C2C12 differentiation. RNA interference was used to reveal the important role of Myf5 in myogenesis inhibited by salidroside. Chromatin Immunoprecipitation and dual-luciferase reporter assay were utilized to explore the underlying mechanisms of salidroside-induced upregulation of Myf5.Results: We found that salidroside inhibits myogenesis by downregulating MyoD and myogenin, preserves undifferentiated reserve cell pools by upregulating Myf5. Knocking down Myf5 expression significantly rescued the myogenesis inhibited by salidroside. The effect of salidroside on myogenesis was associated with increased phosphorylated Smad3 (p-Smad3). Both SIS3 (Specific inhibitor of p-Smad3) and dominant negative Smad3 plasmid (DN-Smad3) attenuated the inhibitory effect of salidroside on C2C12 differentiation. Moreover, the induction of Myf5 transcription by salidroside was dependent on a Smad-binding site in the promoter region of Myf5 gene.Conclusion and Implications: Our findings identify a novel role and mechanism for salidroside in regulating myogenesis through p-Smad3-induced Myf5 transcription, which may have implications for its further application in combating degenerative muscular diseases caused by depletion of muscle stem cells, such as Duchenne muscular dystrophy or sarcopenia.